Letters written during a short residence in Sweden, Norway, and Denmark - Wollstonecraft, Mary, 1759-1797.; Brekke, Tone.; Mee, Jon. (Oxford ; New York : Oxford University Press, 2009)
Letters written during a short residence in Sweden, Norway, and Denmark (1796) is both an arresting travel book and a personal memoir. In it Wollstonecraft describes the sublime landscape and the events and people she encounters. This edition includes reviews, additional letters, and documents on the background to the journey. - ;'If ever there was a book calculated to make a man in love with its author, this appears to me to be the book.'William Godwin, the author's future husband, was not alone in admiring Letters written during a short residence in Sweden, Norway, and Denmark, Wollstonecraf.
Introduction; Note on the Text; Select Bibliography; A Chronology of Mary Wollstonecraft; Map: Mary Wollstonecraft's journey through Scandinavia; LETTERS WRITTEN DURING A SHORT RESIDENCE IN SWEDEN, NORWAY, AND DENMARK; Appendix 1: Wollstonecraft's Commission from Imlay; Appendix 2: Wollstonecraft's Letter to the Danish Prime Minister, Count Bernstorff; Appendix 3: Wollstonecraft's Letters to Imlay; Appendix 4: From William Godwin, Memoirs of the Author of A Vindication of the Rights of Woman; Appendix 5: Contemporary Reviews; Explanatory Notes
Includes bibliographical references (pages xxx-xxvi).
Print version record.
English.
eBooks on EBSCOhost
Keywords: Wollstonecraft, Mary, -- 1759-1797 -- Travel -- Scandinavia; Wollstonecraft, Mary, -- 1759-1797.; Imlay, Gilbert, -- 1754?-1828?; Wollstonecraft, Mary, -- 1759-1797; Correspondence (Wollstonecraft, Mary); Scandinavia -- Description and travel -- Early works to 1800.; Authors, English -- 18th century -- Correspondence; Feminists -- Great Britain -- Correspondence; Scandinavie -- Descriptions et voyages -- Ouvrages avant 1800.; Écrivains anglais -- 18e siècle -- Correspondance; Féministes -- Grande-Bretagne -- Correspondance; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; Authors, English; Feminists; Travel; Great Britain; Scandinavia; 1700-1799; autobiographies (literary works); Autobiographies; Early works; Personal correspondence; Autobiographies; Autobiographies